The relationship of the guilty conscience with the psychological health among the students of the University of Baghdad (Journal Of Educational and Psychological Researches, 2013)
On of the psychological disorders that the human encounters is guilty conscience, this feeling is negative and affects on the individual and on those around him and harms the psychological health of the individual.      since the university students slice is one of the important slices in the community which the country dependes on their abilities , their energies and their faculties in the construction and development, the university professors and specialists in the field of education and psychology who are around them should help them in achieving psychological balance and adjustment with themselves and with others, the following research objectives have been set :  1.Building measurement of guilty conscience among university students.• 2. Building measurement of psychological health of university students.• 3. Identifying the level of guilty conscience among the students of the University of Baghdad.• 4. Identifying the level of psychological health among the students of the University of Baghdad.• 5. Identifying the relationship of the guilty conscience with the psychological health among the students of the University of Baghdad.     The sample of the research included (200) university students were randomly selected from colleges of the scientific and humanitarian  specialties at the University of Baghdad, the items of guilty conscience measurement has been arranged of (40) items, and the items of psychological health measurement has been arranged and it also includes (40) items , after the use of statistical methods the results showed the following :• 1. The results of the first and the second goal indicate to the effectiveness of the measurement of guilty conscience and psychological health measurement in the measure and extraction results in several statistical ways.• 2. The results of the third goal indicate that medium percentage and not low, amounting (75.5%) of university students suffer from guilty conscience .• 3. The results of the fourth goal also indicate to a medium percentage of amounting (77.5%) of students have bad compatibility in psychological health.• 4. The results of the fifth goal indicate to the negative inverse existence relationship between guilty conscience and psychological health, and in light of the following results and the researcher put some appropriate recommendations and proposals.